Association of Spectral-Domain OCT With Long-term Disability Worsening in Multiple Sclerosis. (20th April 2021) - Lambe, Jeffrey; Fitzgerald, Kathryn C.; Murphy, Olwen C.; Filippatou, Angeliki G.; Sotirchos, Elias S.; Kalaitzidis, Grigorios; Vasileiou, Elena; Pellegrini, Nicole; Ogbuokiri, Esther; Toliver, Brandon; Luciano, Nicholas J.; Davis, Simidele; et al.
Abstract : Objective: To evaluate whether a retinal spectral-domain optical coherence tomography (SD-OCT) assessment at baseline is associated with long-term disability worsening in people with multiple sclerosis (PwMS), we performed SD-OCT and Expanded Disability Status Scale (EDSS) assessments among 132 PwMS at baseline and at a median of 10 years later. Methods: In this prospective, longitudinal study, participants underwent SD-OCT, EDSS, and visual acuity (VA) assessments at baseline and at follow-up. Statistical analyses were performed using generalized linear regression models, adjusted for age, sex, race, multiple sclerosis (MS) subtype, and baseline disability. We defined clinically meaningful EDSS worsening as an increase of ≥2.0 if baseline EDSS score was <6.0 or an increase of ≥1.0 if baseline EDSS score was ≥6.0. Results: A total of 132 PwMS (mean age 43 years; 106 patients with relapsing-remitting MS) were included in analyses. Median duration of follow-up was 10.4 years. In multivariable models excluding eyes with prior optic neuritis, relative to patients with an average baseline ganglion cell + inner plexiform layer (GCIPL) thickness ≥70 µm (the mean GCIPL thickness of all eyes at baseline), an average baseline GCIPL thickness <70 µm was associated with a 4-fold increased odds of meaningful EDSS worsening (adjusted odds ratio [OR] 3.97, 95% confidence interval [CI] 1.24–12.70; p = 0.02) and an almost 3-fold increased odds of low-contrast VA worsening (adjusted OR 2.93, 95% CI 1.40–6.13; p = 0.04). Conclusions: Lower baseline GCIPL thickness on SD-OCT is independently associated with long-term disability worsening in MS. Accordingly, SD-OCT at a single time point may help guide therapeutic decision-making among individual PwMS. Classification of Evidence: This study provides Class I evidence that lower baseline GCIPL thickness on SD-OCT is independently associated with long-term disability worsening in MS.